2013
DOI: 10.1016/j.neurobiolaging.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Imaging microglial activation and glucose consumption in a mouse model of Alzheimer's disease

Abstract: Abstract. In Alzheimer´s disease (AD), persistent microglial activation as sign of chronic neuroinflammation contributes to disease progression. Our study aimed to in vivo visualize and quantify microglial activation in 13-to 15-month-old AD mice using [ 11 C]-(R)-PK11195 and positron emission tomography (PET). We attempted to modulate neuroinflammation by subjecting the animals to an anti-inflammatory treatment with pioglitazone (5-weeks' treatment, 5-week wash-out period).[ 11 C]-(R)-PK11195 distribution vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 40 publications
(42 reference statements)
1
39
0
Order By: Relevance
“…Hypometabolism may be associated with the neurodegeneration present in these models. By contrast, aged APPswe/PS1d9 animals (13-15 months) show normal [ 18 F]FDG uptake, whereas the APP751sl/PS1 model showed hypermetabolism despite its higher degree of neuronal depletion [105,106]. The hypermetabolism exhibited by the aged APP751sl/PS1 animals may be linked to the significant inflammatory reaction present in this model.…”
Section: Feature Reviewmentioning
confidence: 81%
“…Hypometabolism may be associated with the neurodegeneration present in these models. By contrast, aged APPswe/PS1d9 animals (13-15 months) show normal [ 18 F]FDG uptake, whereas the APP751sl/PS1 model showed hypermetabolism despite its higher degree of neuronal depletion [105,106]. The hypermetabolism exhibited by the aged APP751sl/PS1 animals may be linked to the significant inflammatory reaction present in this model.…”
Section: Feature Reviewmentioning
confidence: 81%
“…For example, the role of oxidative stress by reactive oxygen species (Van Everbroeck et al, 2004) and microglial toxicity (Brown, 2001; Amor et al, 2010) has been shown in prion diseases, as well as in Alzheimer's disease (Rapic et al, 2013; Heneka et al, 2015; Matsumura et al, 2015), Parkinson's disease (Aras et al, 2014; Borrajo et al, 2014; Kim et al, 2015) and Huntington's disease (Crotti et al, 2014; Rotblat et al, 2014). Specifically, early oxidative stress causing lipid peroxidation is linked to propagation of pathologic prion protein accumulation and to typical neuropathological changes in prion disease (Brazier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A significant age-dependent increase in specific [ 3 H](R)-PK11195 binding was demonstrated in a transgenic mouse model of AD by autoradiography (TASTPM: APP sw xPS1 M146V ; [13]). However, [ 11 C]-(R)-PK11195 positron emission tomography could not demonstrate differences between wild-types and transgenic APP/PS1 mice [14]. This tracer has some limitations, such as high non-specific binding and high binding to plasma proteins.…”
Section: Modelling Alzheimer’s Diseasementioning
confidence: 99%